MENINGKATKAN KONSEP MENGENAL BILANGAN ANAK USIA 3-4 TAHUN MELALUI PERMAINAN TRADISIONAL DAKON DI PAUD AL – FIRDAUS KABUPATEN PROBOLINGGO - kulsum, umi; Warih Windasari, Indriana (LPPM IAD Probolinggo, 2024)
The aims of this research is to improve the concept of recognizing numbers to children using appropriate and fun games. The dakon game is one of the traditional tools that can stimulate the development of the concept of number in early childhood. The game is designed according to the child's age development stage. The research was conducted at PAUD AL-FIRDAUS from May to June 2023.In the research, researchers used Classroom Action Research which is often known as Classroom Action Research. PTK research is carried out through stages 1.Planning 2.Implementation 3.Observation 4.Reflection. The subject of this research was group A which amounted to 23 children. Data collection techniques using observation sheets and documentation, The results of data analysis obtained an average number concept before pre-action of 21.7%. Cycle 1 meeting 1 amounted to 37.9%, meeting 2 amounted to 50% resulting in an average of 44.5% This indicates that this class action was not successful because the target exceeded 75%, .therefore the research was continued in cycle 2. In cycle 2 session 1 reached 77% session 2 reached 95% and an average of 85%. Based on the data analysis of Cycle 2 session 1 and 2, the anticipated goal was declared achieved. From the above statement, it is concluded that using the traditional dakon game media, the ability to recognize the concept of number has improved well. Key words: Number concept; Dakon Traditional Game; Children aged 3-4 years